Alzheimer's disease and periodontitis - an elusive link - Gurav,Abhijit N. (2014)
Alzheimer's disease is the preeminent cause and commonest form of dementia. It is clinically characterized by a progressive descent in the cognitive function, which commences with deterioration in memory. The exact etiology and pathophysiologic mechanism of Alzheimer's disease is still not fully understood. However it is hypothesized that, neuroinflammation plays a critical role in the pathogenesis of Alzheimer's disease. Alzheimer's disease is marked by salient inflammatory features, characterized by microglial activation and escalation in the levels of pro-inflammatory cytokines in the affected regions. Studies have suggested a probable role of systemic infection conducing to inflammatory status of the central nervous system. Periodontitis is common oral infection affiliated with gram negative, anaerobic bacteria, capable of orchestrating localized and systemic infections in the subject. Periodontitis is known to elicit a "low grade systemic inflammation" by release of pro-inflammatory cytokines into systemic circulation. This review elucidates the possible role of periodontitis in exacerbating Alzheimer's disease. Periodontitis may bear the potential to affect the onset and progression of Alzheimer's disease. Periodontitis shares the two important features of Alzheimer's disease namely oxidative damage and inflammation, which are exhibited in the brain pathology of Alzheimer's disease. Periodontitis can be treated and hence it is a modifiable risk factor for Alzheimer's disease.